Correction: p-Type conductivity mechanism and defect structure of nitrogen-doped LiNbO3 from first-principles calculations. Issue 3 (9th January 2020) - Wang, Weiwei; Zhong, Yang; Zheng, Dahuai; Liu, Hongde; Kong, Yongfa; Zhang, Lixin; Rupp, Romano; Xu, Jingjun
Abstract : Correction for 'p-Type conductivity mechanism and defect structure of nitrogen-doped LiNbO3 from first-principles calculations' by Weiwei Wang et al., Phys. Chem. Chem. Phys., 2020, 22, 20–27.